Single-Channel Seismic Images from the Eastern Caribbean Sea and the Western North Atlantic Ocean acquired during the R/V Robert D. Conrad expedition RC2102 (1977) (IEDA: Marine-Geo Digital Library, 2004)
This data set was acquired with the LDEO Single-Channel Seismic system during R/V Robert D. Conrad expedition RC2102 conducted in 1977 (Chief Scientist: Dr. George Bryan). These data files are of JPEG format and include Single-Channel Reflection Seismic images that have not been processed after acquisition. Funding was provided by NSF grants: UC-NSF-C482-2 scope J and OCE76-82326.